Mechanisms of miR-18a-5p Target NEDD9-Mediated Suppression of H5N1 Influenza Virus in Mammalian and Avian Hosts - Jipu Wang; Yanan Xing; Lin Chen; Shuyi Han; Ye Wang; Zhilei Zhao; Gaojian Li; Wenchao Li; Hongxuan He (Veterinary Sciences)
MicroRNAs (miRNAs) are key regulators of gene expression, exerting post-translational control through mRNA silencing or degradation. These molecules play pivotal roles in host–pathogen interactions, particularly in modulating antiviral immune responses. The global public health threat posed by the H5N1 Highly Pathogenic Avian Influenza (HPAI) virus necessitates urgent exploration of novel therapeutic strategies. Our investigation revealed significant dysregulation of miR-18a-5p following influenza virus infection, observed consistently across both in vitro and in vivo models. Experimental evidence demonstrated that miR-18a-5p overexpression effectively inhibits H5N1 virus propagation through multiple mechanisms: (1) in vitro studies using A549 cells transfected with miR-18a-5p mimics showed a substantial reduction in viral replication; (2) animal models (mice and chickens) with elevated miR-18a-5p expression exhibited markedly suppressed AIV replication, reduced pathogenicity, and improved survival rates. The therapeutic potential of miR-18a-5p was particularly evident in its ability to significantly decrease mortality rates in H5N1-infected animals. Furthermore, this miRNA demonstrated robust protective effects against virus-induced lung damage, suggesting its dual role in both preventing and treating H5N1 infections. These findings position miR-18a-5p as a promising candidate for the development of broad-spectrum antiviral interventions, offering a novel strategic approach to combat this serious public health challenge.